Muslim-Friendly or Market-Exclusive? Managing the Paradox of Religious Assurance, Market Openness, and Destination Competitiveness in Halal Tourism - Ryan Irianto Rakhman (Punggawa Legacy Center, 2026)
Muslim-friendly tourism has become a strategic field in Islamic business management, yet its managerial problem is often reduced to the availability of halal facilities and destination branding. Such a view leaves a more difficult tension underexamined. Faith-sensitive services can widen access for Muslim travellers, while the same services may narrow destination appeal once they are framed as a closed market identity. Using qualitative secondary-data research and conceptual-comparative document analysis, this study examines Muslim-friendly tourism across Muslim-majority and non-OIC destinations, with attention to policy materials, industry reports, destination-facing texts, and academic literature. The analysis identifies two contrasting sources of managerial credibility. Malaysia and Indonesia draw on institutional halal legitimacy, while Singapore and Thailand rely more heavily on designed service credibility within plural tourism settings. The findings suggest that Muslim-friendly tourism works best as service architecture rather than religious labelling. Halal food verification, prayer access, staff literacy, digital information, and mobility planning need to connect across the visitor journey. A market-exclusivity trap emerges when halal branding turns these services into a total destination identity and makes wider hospitality less visible. The proposed concept of inclusive Muslim-friendly destination management connects faith-based service assurance, plural market openness, and destination competitiveness. Within Islamic business management, maqāṣid al-sharī‘ah gains operational value when protection of faith is linked to trust, fair access, consumer clarity, and non-exclusionary hospitality.